Improvement of Educational Products Validation form in professional postgraduate programs - Karina Franco Zihlmann; Maria Cristina Mazzaia
ABSTRACT Educational Product and Technical-Technological Product constitute a specificity of postgraduate programs in the professional modality, a product that must be carefully evaluated by the programs and recorded on platforms of evaluating bodies. In 2019, a working group from the teaching area was assembled to create a Validation Form for these products. Thus, this article aims to present a proposal for improving this Validation Form for Educational/Technical-Technological Products, based on reflections treated in scientific articles and scientific events from the area, focusing on the relevance and need for this type of evaluation in a standardized way. It is intended to collaborate with the improvement of the evaluation processes and procedures of Educational/Technical-Technological Products for the necessary accuracy, representativeness, and homogeneity, which will allow the real dimensioning of the contributions of these products. This involves not only training qualified professionals, but also transforming practices in the Sistema Único de Saúde (SUS) [Brazil's Unified Health System], promoting advances in science and in its fields of application.